2023
DOI: 10.1111/1749-4877.12752
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and abiotic stresses on honeybee health

Abstract: Honeybees are the most critical pollinators providing key ecosystem services that underpin crop production and sustainable agriculture. Amidst a backdrop of rapid global change, this eusocial insect encounters a succession of stressors during nesting, foraging, and pollination. Ectoparasitic mites, together with vectored viruses, have been recognized as central biotic threats to honeybee health, while the spread of invasive giant hornets and small hive beetles also increasingly threatens colonies worldwide. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 219 publications
(416 reference statements)
0
0
0
Order By: Relevance
“…Varroa destructor is an arthropod that has a profound impact on honey bee populations, causing significant losses and serving as a vector for various diseases within bee colonies (Rehm & Ritter, 1989;Anderson & Truman, 2000;Morse & Fluton, 1997;Lamas et al, 2023). The mite shows genomic variation at the subspecies level, and each of them has different levels of detrimental impacts on the honey bees (Anderson & Trueman, 2000;Hua et al, 2023;Zheguang et al, 2023). Today, various methods such as heat applications, biological, genetic breeding and biotechnological approaches are employed in the management of Varroa infestations (Kumova, 2004;Girişgin et al, 2007;Çetin, 2010;Koşat, 2016;Guler, 2017;Çakmak, 2017;Seven et al, 2017;Aydın, 2018;Demirezen, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Varroa destructor is an arthropod that has a profound impact on honey bee populations, causing significant losses and serving as a vector for various diseases within bee colonies (Rehm & Ritter, 1989;Anderson & Truman, 2000;Morse & Fluton, 1997;Lamas et al, 2023). The mite shows genomic variation at the subspecies level, and each of them has different levels of detrimental impacts on the honey bees (Anderson & Trueman, 2000;Hua et al, 2023;Zheguang et al, 2023). Today, various methods such as heat applications, biological, genetic breeding and biotechnological approaches are employed in the management of Varroa infestations (Kumova, 2004;Girişgin et al, 2007;Çetin, 2010;Koşat, 2016;Guler, 2017;Çakmak, 2017;Seven et al, 2017;Aydın, 2018;Demirezen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These activities include toxicity, repellant or attraction, reproductive inhibition, behavioral disorder and growth regulatory effects. However, it has been reported that some organic or synthetic drugs and industrial carbohydrates negatively affect the colonies, causing stress and worker bee deaths (Guler et al, 2018;Nisbet et al, 2018a;Bava et al, 2023;Zheguang et al, 2023). For example, high doses of thymol can induce genomic cell poisoning (Glavini´c et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations